TiO2 loaded on reduced graphene oxide nanosheets as efficient electrodes in Dye-sensitized solar cell / Low Foo Wah - Low , Foo Wah (2018)
The formation of graphene oxide (GO) and reduced graphene oxide (rGO) nanosheet are a vital two dimensional (2D) material for highly efficient in dye-sensitized solar cell (DSSC) application. Comprehensive investigations on different parameters were conducted in order to control lateral size of nanosheet. Highly carbon content and thin film of rGO nanosheet in thickness controlled were successfully synthesized under 72 h and 1200 rpm, respectively. In specific, the large production and thin film of rGO nanosheet (≈46 nm) was achieved under high speed of 1200 rpm and 72 h reaction time. Continuous efforts have been exerted to further improve the power conversion efficiency (PCE) of DSSC performance by incorporating an optimum content of Titanium Dioxide (TiO2) with rGO nanosheet using one-step hydrothermal and advanced implantation techniques in order to facilitate the injected electrons from N719 dye to the conduction band of TiO2 and rGO based on its Fermi Level. It was found that optimum TiO2 content of 0.3% incorporated with rGO nanosheet via one-step hydrothermal technique established well Ti-O-C bonds and achieved photocurrent density of ≈28.36 mA/cm2 with PCE ≈7.20%. However, another useful ion implantation technique was applied which Ti3+ ions were sputtered onto rGO nanosheet with sputtering duration at 40s and lastly achieved the maximum PCE ≈8.78%. Herein, the higher performance of TiO2-rGO nanocomposite (NC) as photoanode in DSSC application with advanced implantation technique than one-step hydrothermal technique (improved of 3.17%). These findings revealed that the Ti3+ ions species have been modified by rGO surface and even its lattice by high applied power (advanced implantation technique). Furthermore, the electron transfer rate was also noted to be the fastest due to the highest availability of the carbon-atom vacancy holes for Ti3+ replacement. On top of that, it may assigned that Ti3+ ion was fully loaded onto rGO nanosheet leading to the highest interactions with the O-H functional group in NC or Ti3+ could react with the epoxide or phenolic groups in rGO forming the Ti-O-C/Ti-O-Ti bonds. Besides, the incorporated of rGO with Ti3+ ions by calcination reaction (one-step hydrothermal technique) was gained lower PCE as compared with advanced implantation technique due to the higher electron-hole pairs charge recombination and thus increases of interior resistance. However, the excess incorporation of Ti3+ ions content (0.4 wt%, 0.5 wt%, 200 W, 250 W, 60s) onto rGO lattice leading poor PCE attributed to the over photocatalytic reation occurred leaving extra holes on the counter electrode and hence increased the charge transport resistance at the KI electrolyte/N719 dye/rGO/TiO2 interfaces.